Dynamics of variability in agronomic characters of millet cv. ‘Gorlinka’ under the climate conditions of the southern part of the East European Plain - T. V. Kulemina (Труды по прикладной ботанике, генетике и селекции)
Background. The change of temperature conditions is cyclic by nature. Since the 1970s this process has been intensifying several times faster towards global climate warming. The effect of high temperature and drought is expected to lead to undesirable consequences for the economy, a decrease in yields, and a threat to food security. This aspect requires an assessment of the ongoing climate changes and identification of the causes that induce the response of plants to them.Materials and methods. The zoned millet cultivar ‘Gorlinka’ served as the material for this study. Variability was assessed from 2001 through 2019 for such characters as the duration of the growing season, grain yield, grain size, and plant height. The cultivar was tested according to VIR’s guidelines. Statistical data processing was performed using Microsoft Excel.Results and conclusion. The climate change in the southern part of the East European Plain (Tambov Province) from 2001 to 2019 towards warming in June under sufficient moisture (HTC = 1.26) did not significantly affect the duration of the growing season or grain yield of cv. ‘Gorlinka’.